10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Doxorubicin (DOX) is a common anticancer drug used to treat various types of neoplasms. However, its use is associated with neurotoxic effects, including neuronal degeneration and damage. OBJECTIVE: The principal objective of the current experiment was to examine the mechanisms underlying biochemical and histological brain alterations induced by DOX under acute experimental conditions. Moreover, the ameliorative effects of allicin (AC) and/or L-carnitine (LC) against DOX-induced biochemical and histological brain alterations were evaluated. METHODS: A total of seven groups of Wistar rats (n = 49; male, 150 ± 50 g; 30 weeks old) were established, including the control, AC, LC, DOX, AC+DOX, LC+DOX and AC+LC+DOX groups. Biochemical analyses, oxidative stress and proinflammatory cytokines were assessed spectrophotometrically using ELISA, and the histomorphology of brain sections (cerebrum, cerebellum and hypothalamus) was evaluated. RESULTS: Results revealed that treatment with DOX increased acetylcholinesterase (AChE) activity (p < 0.0001) with increased levels of malondialdehyde (MDA) and nitric oxide (NO) contents. Meanwhile, non-enzymatic (glutathione, GSH) levels and enzymatic (superoxide dismutase, SOD; catalase, CAT) antioxidant activities were decreased. In addition, acute experimental DOX conditions increased levels of proinflammatory cytokines and interleukins (ILs): IL-6 and IL-1β. Histopathologically, the brain sections showed neuronal degeneration and vacuolization. However, biochemical, oxidative, inflammatory and histological brain alterations caused by acute experimental DOX conditions were improved by AC and/or LC supplementation. CONCLUSION: In summary, our research showed that AC and/or LC attenuated acute DOX-associated biochemical, oxidative, inflammatory and histological brain alterations.